2011
DOI: 10.1371/journal.pone.0016456
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury Causes Sustained Disruption of the Blood-Testis Barrier in the Rat

Abstract: There is a high incidence of infertility in males following traumatic spinal cord injury (SCI). Quality of semen is frequently poor in these patients, but the pathophysiological mechanism(s) causing this are not known. Blood-testis barrier (BTB) integrity following SCI has not previously been examined. The objective of this study was to characterize the effects of spinal contusion injury on the BTB in the rat. 63 adult, male Sprague Dawley rats received SCI (n = 28), laminectomy only (n = 7) or served as uninj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Animals received a laminectomy at spinal cord thoracic level 10 (T10), and the vertebral column was stabilized at T9 and T11. A moderate contusion injury (150 kdynes of force with 1 s dwell) was delivered to the spinal cord at T10 using the Infinite Horizon Impactor (Precision Systems and Instrumentation, LLC, Fairfax Station, VA), without opening the dura mater (Scheff et al, 2003; Dulin et al, 2011). The overlying muscles were immediately sutured and the skin was closed with stainless steel wound clips.…”
Section: Methodsmentioning
confidence: 99%
“…Animals received a laminectomy at spinal cord thoracic level 10 (T10), and the vertebral column was stabilized at T9 and T11. A moderate contusion injury (150 kdynes of force with 1 s dwell) was delivered to the spinal cord at T10 using the Infinite Horizon Impactor (Precision Systems and Instrumentation, LLC, Fairfax Station, VA), without opening the dura mater (Scheff et al, 2003; Dulin et al, 2011). The overlying muscles were immediately sutured and the skin was closed with stainless steel wound clips.…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory response after SCI has been associated with tight junction disruption within the uroepithelium of the bladder. In an attempt to investigate whether the higher incidence of male infertility following traumatic SCI could be attributed to disruption of the BTB/SC barrier caused by SCI-associated inflammatory response, the integrity of the BTB/SC barrier and autoimmune response after SCI in rats was explored [34]. Increased permeability of the BTB/SC barrier to the small molecular weight molecule, gadopentate dimeglumine, following acute (72hrs) and chronic (10 month) SCI in adult rats indicated that the integrity of the BTB/SC barrier was breached.…”
Section: Blood-testis-barrier/sertoli Cell Barrier and Its Role Inmentioning
confidence: 99%
“…Increased permeability of the BTB/SC barrier to the small molecular weight molecule, gadopentate dimeglumine, following acute (72hrs) and chronic (10 month) SCI in adult rats indicated that the integrity of the BTB/SC barrier was breached. Furthermore, increased antibody deposition, immune cell (mast cells and macrophages) infiltration within the testicular interstitium and seminiferous tubules and germ cell apoptosis in SCI rat testes was observed [34]. Collectively, the BTB/SC barrier creates a conducive environment necessary for completion of spermatogenesis and sequestering the auto-immunogenic germ cells from the immune system.…”
Section: Blood-testis-barrier/sertoli Cell Barrier and Its Role Inmentioning
confidence: 99%
“…76 SCI surgeries were performed as previously described. 77,78 Incisions were made on the animals' dorsal skin and overlying muscles and the vertebral column was exposed. A laminectomy was performed at thoracic level 10 (T10) and the vertebral column was stabilized using forceps that grasp the ventral surface of the lateral spinous processes at vertebral levels T9 and T11.…”
Section: Sci Surgerymentioning
confidence: 99%
“…The primary reason for the use of male rats in the latter studies is our emerging interest on the impact of SCI on the blood-testis barrier, 77 causing our laboratory to switch to the use of male rats during the course of this study. Although previous studies have indicated that there are gender-associated differences in Pgp transport activity in body tissues of experimental animals and humans, 110 we have not yet investigated whether there is a differential impact of SCI on Pgp expression and/or function in male and female rats.…”
Section: Increased P-glycoprotein Expression and Activity In The Injumentioning
confidence: 99%